ENHANCED LEARNING ENVIRONMENT AND ITS IMPLICATIONS ON THE PRE- SCHOOL CHILDREN’S LANGUAGE PERFORMANCE - Okudo, Afoma R.; Omotuyole, Christy (European Scientific Journal, ESJ, 2014)
Play has been commonly accepted as the best language of communication with the pre - school children. In the playful interactions, they utilize play gadgets and materials in their learning environments. Teachers trained for this level have also strongly advocated and emphasized the play- way method with an environment richly enhanced with play gadgets and materials. This study therefore investigated the impact of enhanced learning environment and its implications on the language development and achievement of the pre-school children. Questionnaire was the instrument used to elicit data from one hundred and fifty five pre- school teachers. Stratified random sampling was used to select the respondents for the study from seven local council development areas of Ikorodu local government of Lagos state, Nigeria. Results were analyzed using simple percentages and correlation analysis. The findings of the study depict that the environment of the pre-school children should provide nourishment for the children’s language and overall development and that the content and their learning styles should be quite different from those of the adults.